Biological properties of the Royal Belum Forest Reserve plants - Azlina Aziz (Pusat Penerbitan Universiti (UPENA), Universiti Teknologi MARA, 2019)
A total of 61 plant species were collected at random from the Royal Belum Forest Reserve. The plants were then subjected to cold extraction prior to antimicrobial and cytotoxicity screenings. The results obtained demonstrated that 69% of extracts showed antimicrobial activities and 17% showed cytotoxicity against MCF-7. Based on the results obtained from both antimicrobial and cytotoxic assays, five plants which produced significant bioactivities namely P019, P024, P028, P030 and P108 were selected for further investigation.